Avaliação da quimioprofilaxia como estratégia para vigilância de contatos de hanseníase - GONÇALVES, Ricardo Mendes (2024)
Leprosy remains a public health problem in Brazil and this may be related to the low exploitation of tools that show promise in controlling the disease. Contact chemoprophylaxis uses antibiotics already available through the public health network and is an effective tool for preventing the development of the disease in infected individuals without clinical signs. In parallel, spatial analysis in health has generated a large amount of information about disease transmission and can make it possible to monitor the outcome of chemoprophylaxis interventions. Therefore, the present study aimed to evaluate the effect of chemoprophylaxis as a strategy for surveillance of leprosy contacts in a pioneering study with long-term follow-up in a continental geographical area with a very high endemic level. These are three types of interdependent studies, one cross-sectional, one community intervention and one prospective cohort, carried out in the cities of Açailândia and Imperatriz, in Maranhão. The study began in 2009 and continued until 2019. Healthy contacts of newly diagnosed patients received ROM (Rifampicin, Ofloxacin and Minocycline) in two doses, with an interval of 28 days and were called annually to perform dermatoneurological physical examinations, serological tests, as well as updating addresses for georeferencing purposes. The study demonstrated an average protection of 4.3 times for contacts who underwent chemoprophylaxis compared to those not taking medication. The average effectiveness of the intervention was 76.51%. A stratified analysis showed that effectiveness varies according to the type of contact, reaching up to 100.00% for extra-household contacts (p=0.0081), as well as that chemoprophylaxis presents greater protection in contacts with negative serology (p<0.0001) . Spatial analyzes demonstrated that in the city of Imperatriz, Maranhão, Brazil there was a reduction in the detection coefficient of leprosy cases by 38.4%, as well as a change in the distribution profile of the disease, considering that in 2010 cases were more concentrated, and at the end of the study in 2019 there were fewer clusters and greater dispersion in this distribution. Thus, we demonstrate the importance of chemoprophylaxis with a ROM regimen as a complementary strategy in programs to combat leprosy, especially in highly endemic continental areas. However, more studies need to be carried out to evaluate different therapeutic regimens and dosages of chemoprophylaxis, expanding the application to a greater number of household contacts, as well as expanding the strategies and follow-up period for these individuals, considering the complexity of this type of study and appropriate control of variables that interfere in the final clinical outcome.